A collective decision-making framework for simulating urban land-use planning: An application of game theory with event-driven actors. (June 2022) - Abolhasani, Somaie; Taleai, Mohammad; Lakes, Tobia
Abstract: Since land-use planning has become more participatory, there is a need to develop collective decision-making (CDM) frameworks to support the development of adequate land-use plans. However, in CDM processes the action of a decision-maker affects and is affected by the decisions of others. Therefore, this study aims to develop a game-theoretic collective-interactive decision-making (GTCIDM) framework for urban land-use planning. In GTCIDM, a strategic game is employed to simulate the interrelated behaviour of decision-makers. GTCIDM considers potential consequences of the decisions of decision-makers and defines a consensus on CDM by specifying the self-enforcing Nash equilibrium. This study also employs event-driven actors, who consider time as a continuous current, broken by events. To analyse the importance of the interactive and time-specific decision-making in urban land-use planning, we compare different scenarios of collective-interactive and event-driven decision-making versus non-interactive and static decision-making. We applied the scenarios to data from municipal region 22 of Tehran. The results show that GTCIDM with event-driven actors can achieve more suitable results in comparison to the non-interactive and non-event-driven decision-making processes in terms of land-use planning indicators. Finally, GTCIDM not only yields an insight into the collective-interactive decision-making process but can also support the development of urban land-use plans. Highlights: Introducing a game-theoretic collective-interactive method for urban planning. Employing event-driven actors for urban land-use planning. Non-interactive and non-event-driven decision-making scenarios are implemented. A consensus on group decision-making is defined based on Nash equilibrium.